Anticancer Effect of C19-Position Substituted Geldanamycin Derivatives Targeting NRF2-NQO1-activated Esophageal Squamous Cell Carcinoma - Oshikiri, Hiroyuki; Taguchi, Keiko; Hirose, Wataru; Taniyama, Yusuke; Kamei, Takashi; Siegel, David; Ross, David; Kitson, Russell R A; Baird, Liam; Yamamoto, Masayuki (Molecular and cellular biology, 2025)
In esophageal squamous cell carcinoma, genetic activation of NRF2 increases resistance to chemotherapy and radiotherapy, which results in a significantly worse prognosis for patients. Therefore NRF2-activated cancers create an urgent clinical need to identify new therapeutic options. In this context, we previously identified the geldanamycin family of HSP90 inhibitors, which includes 17DMAG, to be synthetic lethal with NRF2 activity. As the first-generation of geldanamycin-derivative drugs were withdrawn from clinical trials due to hepatotoxicity, we designed second-generation compounds with C19-substituted structures in order to inhibit glutathione conjugation-mediated hepatotoxicity. In this study, using a variety of in vitro and in vivo cancer models, we found that C19-substituted 17DMAG compounds maintain their enhanced toxicity profile and synthetic lethal interaction with NRF2-NQO1-activated cancer cells. Importantly, using a xenograft mouse tumor model, we found that C19-substituted 17DMAG displayed significant anticancer efficacy against NRF2-NQO1-activated cancer cells without causing hepatotoxicity. These results clearly demonstrate the improved clinical potential for this new class of HSP90 inhibitor anticancer drugs, and suggest that patients with NRF2-NQO1-activated esophageal carcinoma may benefit from this novel therapeutic approach.
Keywords: Animals; Female; Benzoquinones; NF-E2-Related Factor 2; Cell Line, Tumor; ESCC; skvamózní karcinom jícnu; ženské pohlaví; Mice, Nude; HSP90 Heat-Shock Proteins; NQO1; lidé; Esophageal Neoplasms; Mice; Antineoplastic Agents; protinádorové látky; NAD(P)H Dehydrogenase (Quinone); benzochinony; faktor 2 související s NF-E2; C19-position substituted geldanamycin derivatives; NAD(P)H dehydrogenasa (chinon); myši; HSP90; nádory jícnu; Lactams, Macrocyclic; xenogenní modely - testy protinádorové aktivity; proteiny tepelného šoku HSP90; makrocyklické laktamy; NRF2-NQO1-activated cancer; Esophageal Squamous Cell Carcinoma; Xenograft Model Antitumor Assays; zvířata; myši nahé; nádorové buněčné linie; Humans